Critical analysis of successful gold exploration methods. (March 2014) - Brown, L.; Vearncombe, J.
<x content-type="archive" xml:space="preserve">Abstract</x> To assess common factors and the key exploration methods in gold discovery we analyse 154 case studies of successful gold exploration. Our aim is to highlight what may help find gold in the future. The case studies used here are only those documented in the consistent series of biennial volumes of New Generation Gold from 1995 to 2013. Surface and near surface sampling dominate early phases of exploration. Subsequently, as a second and third priority drilling, initially rotary air blast or air-core and then reverse circulation and diamond core drilling dominate exploration. The priority order of methods is more or less the order of access from surface. However, some discoveries document reverse circulation or diamond core drilling as the first and primary method suggesting success by bold targeting and early drilling. Gold has no direct recognisable geophysical signature but geophysics is used as an indirect tool to model the geology and weathering. Geophysical methods, be they magnetic or electrical methods, maintain a similar level of interest throughout programmes. Alteration science is recorded as a method in only 13% of discoveries, a comment that may seem at odds with the modern focus on hyperspectral mapping and logging. Similarly and despite being unambiguously the principal control on gold mineralisation, structure is recorded as of use in only 53% of discoveries, usually a 3rd or 4th priority. Of the case studies, 16% make no mention of structure at all. It is surprising that when surface outcrop is available, structural geology is rarely documented as an exploration method. The low levels of reporting of the intellectual activities of alteration and structural geology (and to a lesser extent mapping and geophysics) suggests they are (i) under-reported or, (ii) that current science is inadequate (this is unlikely) or, (iii) they are under-utilised. If under-reported, are the senior managers and directors who wrote these papers aware of the intellectual effort of their teams? Alternatively if under-used, alteration and structure may represent a significant opportunity for the next generation of exploration.